Translation Types and Strategies Applied by Sari Kusuma in Translating Alexander McCall Smithâs The Girl Who Married a Lion into Gadis yang Menikahi Seekor Singa - Fajria, Astry (Universitas Ahmad Dahlan, 2015)
Translation deals with literary and non-literary texts. Translating literary texts involves not only the language but also the cultural aspect of the text. A compilation of short stories written by Alexander McCall Smith entitled The Girl Who Married a Lion and the translation by Sari Kusuma entitled Gadis yang Menikahi Seekor Singa is interesting to discuss because it contains many stories, including fairy tales and fables. Hence, the short stories are fully loaded with cultural aspect, which thereby affects the way the work is translated. Thus, this article is to reveal the translation types, structure, and strategies applied by the translator in translating the short stories.Keywords: translation types, translation strategy, Alexander McCall